THEORICAL REVIEW: SOCIAL RESPONSES TO COMMUNICATION TECHNOLOGIES THEORY (SRCT THEORY) - Felisianus Efrem Jelahut; Yosef Emanuel Jelahut; Lasarus Jehamat (Fakultas Dakwah dan Komunikasi, 2021)
This research is a review of a theory in media communication that plays an important role in analyzing the impact of computers and other technologies on human social life. The theory reviewed in this study is the Theory of Social Responses to Communication Technologies. This theory talks about the human response to interactive communication technology with a number of behaviors and attitudes that are determined by the same social rules and expectations that apply when communicating with other humans. The figure who initiated this theory was Clifford Nass. Born on April 3, 1958 in New Jersey - United States. The purpose of this study is to review a media communication theory. This study uses a qualitative method with a literature study approach that investigates the work of the theory initiator, Clifford Nass. The results of the research are a complete description of the theory which consists of figures who initiate theories, history, theoretical models, definitions and assumptions as well as examples of the application of theory in scientific research